DYNAMIC BEHAVIOR OF FLEXIBLE PLATES SUPPORTED BY A TRANSVERSELY ISOTROPIC HALF-SPACE - Guerra, Conrado Segalla; Barros, Pérsio Leister de Almeida; Pavanello, Renato (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The analysis of flexible plates supported on single layered soil usually uses the Winkler model to simulate the displacements and soil pressure on the plate. However, this model presents serious limitations and it is not able to represent the lateral continuity of the soil. In this article a formulation for the analysis of flexible plates under harmonic dynamic loading, supported on the soil surface, modeled as homogeneous elastic, transversely isotropic half-space is shown. The plate is modeled by rectangular finite elements (FEM) and for the soil the indirect boundary element method (IBEM is used). Dynamic influence functions are used for the elastic transversely isotropic half-space. Therefore, only the interface soil-plate is discretized. The compatibility of the displacements between the plate elements and the soil elements is done in the central point of those elements. Hence, the discretization of the plate and the soil surface in contact are the same. Numerical results for rectangular plates supported by isotropic medium are compared with published results by other authors. The anisotropic effect of the soil in the system is also analyzed.